Association between sleep duration and burnout in healthcare professionals: a cross-sectional survey - Jacksaint Saintila; Anderson N. Soriano-Moreno; Cristian Ramos-Vera; Susan M. Oblitas-Guerrero; Yaquelin E. Calizaya-Milla (Frontiers in Public Health, 2024)
BackgroundShort sleep duration in healthcare professionals is a recurring concern among researchers. On the other hand, the prevalence of burnout in this population group is experiencing exponential growth. Therefore, this study aimed to explore the association between sleep duration and burnout in healthcare professionals.MethodsThis is a cross-sectional study. Data were collected by applying a non-probabilistic convenience sampling, considering a sample of 300 healthcare professionals from the public sector in Peru. The association between variables was explored using multivariate logistic regression. Values of p < 0.05 were considered statistically significant.ResultsThe results of the analysis in the crude models revealed that both men and women who slept < 7 h during workdays and days off were 8.33 (95% CI = 2.68–13.99, p = 0.004) and 17.18 (95% CI = 10.50–23.87, p < 0.001) times more likely to have burnout compared to those who reported ≥7 h, respectively. After adjusting for confounding variables, the association remained statistically significant.ConclusionThe findings of this study underscore the critical importance of sleep duration in the incidence of burnout among healthcare professionals. In the context of the global challenges to the mental and physical health of these professionals, our results highlight the urgent need to implement strategies at the organizational and individual level. This includes promoting a better work-life balance, and effective stress management and improved sleep quality.